Study on Seismic Behavior of Steel Frame-Steel Shear Wall with Assembled Two-Side Connections. (18th December 2019) - Zhang, Yuben; Zhan, Xun
Abstract : Low-cycle reciprocating loading tests were carried out on a steel frame with prefabricated beam-only connected steel plate shear wall (specimen A) and a steel frame with welded beam-only connected steel plate shear wall (specimen B). The seismic performance of the two different types of steel frame-steel plate shear wall specimens was studied and the failure modes, hysteresis curve, skeleton curve, and seismic performance index, etc of two groups of specimens were obtained, together with the studies of failure characteristics, ductility, energy dissipation, and stiffness degradation of the two specimens. The results showed that the assembled steel frame-steel plate shear wall with connection joints of steel shear wall with discontinuous cover plate connected on both sides (DCPC) have good seismic performance. On the basis of no loss of seismic performance, DCPC joints can provide better energy dissipation capacity than traditional welded steel plate shear wall structures and ensure the good postearthquake repair function.